solve equation (x+1)(x-2)=54

Eric stated that the solution would be (x+1)=54==> x=53 or (x-2)=54==> x=56
However at least one of these solutions fails to work when substituted back in the orginial equation. Why is that? Please help Eric to understand better, solve the problem yourself, and explain your reasoning.

Can someone please help me with this. I need this as soon as possible.

1 answer

Eric is very dense, he does not understand the zero identity.

if a*b=0, either a or b or both are zero.

multiply it out:
x^2-x-2=54
x^2-x-56=0

(x-8)(x+7)=0
x=8, x=-7 in accordance with the zero identity.
Similar Questions
  1. Solve for x to determine if the equation has one, none, or infinite solutions.4x=3(x+5)−15(1 point) Responses The equation has
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Solve for xto determine if the equation has one, none, or infinite solutions. 6(2x+4)−24=12x (1 point) Responses The equation
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions